2012
DOI: 10.1371/journal.ppat.1002628
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Damage during Listeria monocytogenes Infection Triggers a Caspase-7 Dependent Cytoprotective Response

Abstract: The cysteine protease caspase-7 has an established role in the execution of apoptotic cell death, but recent findings also suggest involvement of caspase-7 during the host response to microbial infection. Caspase-7 can be cleaved by the inflammatory caspase, caspase-1, and has been implicated in processing and activation of microbial virulence factors. Thus, caspase-7 function during microbial infection may be complex, and its role in infection and immunity has yet to be fully elucidated. Here we demonstrate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 59 publications
(63 reference statements)
1
32
0
Order By: Relevance
“…Furthermore, the gene expression profiles were differentially regulated by NALPL1 and NALPL2, which was identified by PCR array. In mammals, host activation of caspase-7 can protect membrane integrity during infection with the intracellular bacterial pathogen, Listeria monocytogenes (Cassidy et al, 2012). The induced expression of caspase-7 by NALPL2 in the present study may be attributable to inhibit bacterial invasion through protecting infected cells against plasma membrane damage.…”
Section: Discussionmentioning
confidence: 53%
“…Furthermore, the gene expression profiles were differentially regulated by NALPL1 and NALPL2, which was identified by PCR array. In mammals, host activation of caspase-7 can protect membrane integrity during infection with the intracellular bacterial pathogen, Listeria monocytogenes (Cassidy et al, 2012). The induced expression of caspase-7 by NALPL2 in the present study may be attributable to inhibit bacterial invasion through protecting infected cells against plasma membrane damage.…”
Section: Discussionmentioning
confidence: 53%
“…In the context of C. concisus infection, it is unclear if caspase-7 is involved in apoptosis or the inflammatory response to microbial infection, given that APAF1 (0.39-fold) and several pathways associated with apoptosis were downregulated upon infection and the gene encoding PARP1, a protein that plays a caspase-7-mediated regulatory role in proinflammatory gene expression (47), was also downregulated (0.26-fold) upon infection. Interestingly, caspase-7 activation in response to toxin-mediated membrane damage has been proposed to be an adaptive mechanism by which host cells can maintain membrane integrity during infection (48). Given that C. concisus UNSWCD damages the host cell membrane (18,19) and produces an RTX toxin (repeats in the structural toxin) known to induce membrane pore formation (20), it is possible that the production of this toxin induces caspase-7 upon infection.…”
Section: Resultsmentioning
confidence: 99%
“…Also, a more recent study suggested that LLO perforates the plasma membrane of bone marrow-derived macrophages at late stages of infection. Interestingly, the plasma membrane of caspase 7 −/− macrophages was more damaged, revealing a role for this cysteine protease in maintaining the integrity of infected cells [130]. Therefore, LLO secreted into the cytosol may undergo moderate perforation of host cell membranes affecting the biology of infected cells.…”
Section: Listeriolysin O Is An Intracellular Pore-forming Toxin With mentioning
confidence: 99%